Phonon modes and raman scattering in SixGe1-x nanocrystals: microscopic modelling - Vasin, Alexander (2013)
Si1-xGex nanocrystals (NCs) of different composition and size were generated using the Molecular Dynamics (MD) method by minimizing NC’s total energy calculated using Tersoff’s empirical potential and applying rigid boundary conditions. The dynamical matrix of the relaxed NC was constructed and the NC phonon modes were calculated. The localisation of the principal (Si-Si, Si-Ge and Ge-Ge) modes is investigated by analysing their inverse participation ratio. The dependence of the corresponding Raman spectra, obtained by employing the bond polarisability model, upon x and the NC size is presented and compared to previous calculated results and available experimental data.